Preliminary experience with recanalization of large vessel occlusion due to underlying long-segment dissection using a standby microwire technique - Zhang, Xiaoxi; Xu, Hongye; Feng, Zhengzhe; Hua, Weilong; Shen, Hongjian; Zhang, Lei; Zhang, Yongxin; Xing, Pengfei; Yang, Pengfei; Xu, Xiaolong; Li, Zifu (Frontiers in Neurology, 2022)
Abstract Purpose: This study aimed at investigating a novel standby microwire technique to facilitate revascularization of large vessel occlusion due to underlying long-segment dissection. Methods: Patients with acute ischemic stroke with emergent large vessel occlusion (ELVO) due to underlying long-segment dissection were screened from the prospectively established database. The clinical and radiological data of eligible patients who underwent endovascular treatment by using a standby microwire technique were investigated. Results: Of the 165 acute ischemic stroke patients who underwent mechanical thrombectomy, the standby microwire technique was used in five patients aged 33-55 years old with occlusion due to underlying long-segment dissection. Of them, three patients were diagnosed with tandem lesions and three were located at the anterior circulation. A 300cm exchange microwire was used as the standby microwire. Stent deployment was performed in all five patients. Groin puncture to reperfusion time ranged from 10-68 minutes. Technical success and favorable clinical outcomes were achieved in all five patients (100%). No technique-related complication was observed. Conclusion: Our preliminary experience showed that the standby microwire technique was a useful ancillary approach to facilitate the revascularization of large vessel occlusion due to underlying long-segment dissection.